2016
DOI: 10.3390/nu8040216
|View full text |Cite
|
Sign up to set email alerts
|

The Essentiality of Arachidonic Acid in Infant Development

Abstract: Arachidonic acid (ARA, 20:4n-6) is an n-6 polyunsaturated 20-carbon fatty acid formed by the biosynthesis from linoleic acid (LA, 18:2n-6). This review considers the essential role that ARA plays in infant development. ARA is always present in human milk at a relatively fixed level and is accumulated in tissues throughout the body where it serves several important functions. Without the provision of preformed ARA in human milk or infant formula the growing infant cannot maintain ARA levels from synthetic pathw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
185
2
10

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 287 publications
(220 citation statements)
references
References 285 publications
(444 reference statements)
7
185
2
10
Order By: Relevance
“…During the last 3 decades, there has been considerable interest in the roles of long chain polyunsaturated fatty acids (LCPUFAs) in infant growth and development [1][2][3][4][5][6] . The seminal work of Manuel Martinez [7] showing the rapid accretion of docosahexaenoic acid (DHA) and arachidonic acid (ARA) by the infant brain during the first 1,000 days of life underlined the potential importance of these fatty acids during this critical period of growth and development.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…During the last 3 decades, there has been considerable interest in the roles of long chain polyunsaturated fatty acids (LCPUFAs) in infant growth and development [1][2][3][4][5][6] . The seminal work of Manuel Martinez [7] showing the rapid accretion of docosahexaenoic acid (DHA) and arachidonic acid (ARA) by the infant brain during the first 1,000 days of life underlined the potential importance of these fatty acids during this critical period of growth and development.…”
Section: Introductionmentioning
confidence: 99%
“…There is now a wealth of information on the roles of ARA and DHA from cellular, animal and human studies and it is evident that in early life, adequate supplies of both ARA and DHA are critical for normal growth and development [4,5] . However, much of the available research data has been generated in high-income countries and there is currently limited information on dietary intakes of ARA and DHA by infants and young children living in medium-to low-income countries.…”
Section: Introductionmentioning
confidence: 99%
“…However, the neurons appeared less matured and differentiated in the Plaa À/À embryos ( Figs 6B and 7C). The role of PGE 2 in bradykinininduced neuroprotection has been reported in microglial and neuronal cells (Hadley et al, 2016). The reduced production of PGE 2 in the Plaa À/À embryos brain (Fig.…”
Section: Mouse Model Inactivation Of the Plaa Gene Results In Perinatmentioning
confidence: 70%
“…In contrast to this, we observed that Elovl2 / mothers fed a DHA-enriched diet had a lower level of successful pregnancies (Table 3). Regarding the Elovl2 / genotype, which is a model system reflecting insufficient conversion of EPA into DHA, we observed relatively high maternal levels of EPA under standard conditions, which upon dietary supplementation, became even higher (supplemental Tables S16-S19) and may have a negative effect on pregnancy outcome (49,50). Nevertheless, this hypothesis needs to be supported by further and more detailed studies.…”
Section: Discussionmentioning
confidence: 68%